Gastrochilus dulongjiangensis (Aeridinae, Vandeae, Epidendroideae, Orchidaceae), a new species from Yunnan Province, China - Liu, Qiang; Gao, Jiang-Yun (Phytotaxa, 2018)
Gastrochilus dulongjiangensis, a new species from Gaoligongshan National Natural Reserve, Yunnan, China, is described here. It is morphologically similar to G. pseudodistichus and G. fuscopunctatus, but can be distinguished from them by having the orbicular epichile, hypochile as wide as epichile and fusiform pollinia. A preliminary risk-of-extinction assessment shows that the new species should be regarded as Data Deficient (DD) according to the IUCN Red List Categories and Criteria.